Estudo de associação de polimorfismos nos genes APOC1, BAT1 e ABCG2 na doença de Alzheimer - Almeida, Leila Dias de (2014)
Alzheimer's disease (AD), a progressive neurodegenerative disorder, is considered the most common form of dementia. This disease can occur sporadically or have familial recurrence. More than 90% of AD patients develop the disease sporadically and with late onset. In such cases, the disease has a multifactorial etiology, since it is related to aging, genetic factors, environmental factors and behavioral activities to which the patient is exposed. Several genetic polymorphisms have been studied worldwide in order to verify their association with AD. Studies such as this should be done in different communities in order to create a genetic risk profile for specific populations. The polymorphisms APOC1 H2, BAT1-22 and ABCG2 C421A were analyzed using the PCR-RFLP technique and case: control study, in order to evaluate the risk potential of these genetic variations for AD in Vitória-ES population The H1 / H1 APOC1 genotype showed statistically significant values (OR = 0.186, 95% CI = 0044-0777; P = 0.021), behaving as a protective factor against the disease in the population concerned. The other polymorphisms didn’t show any association with AD. Polymorphisms APOC1 H2, BAT1-22 and ABCG2 C421A were also investigated in other populations, where they showed different results from the ones in this research. It is suggested that such differences could be explained by existing ethnic differences among populations.